2015
DOI: 10.1016/j.jad.2015.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of self-referential processing and implicit self-associations in chronic depression

Abstract: The distinct neural processing of emotional self-relevant stimuli in the mPFC and the dlPFC in patients with cMDD might represent an emotional blunting response towards negative self-relevant stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…In addition, recent evidence demonstrated the validity of the CCBH for depression [41] by showing an interdependence of interpretation, memory, and attention in participants with subclinical depression. Furthermore, it was demonstrated that patients with depression are sensitive to a depression symptom IAT accompanied by aberrant activity in medial prefrontal cortex and DLPFC [35]. These results suggest that patients with depression represent an adequate clinical control group to investigate the specificity of an implicit bias for body-symptom words in PHA.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, recent evidence demonstrated the validity of the CCBH for depression [41] by showing an interdependence of interpretation, memory, and attention in participants with subclinical depression. Furthermore, it was demonstrated that patients with depression are sensitive to a depression symptom IAT accompanied by aberrant activity in medial prefrontal cortex and DLPFC [35]. These results suggest that patients with depression represent an adequate clinical control group to investigate the specificity of an implicit bias for body-symptom words in PHA.…”
Section: Introductionmentioning
confidence: 84%
“…The amygdala is sensitive to salience [26] and ambiguity [27,28], and is a key structure in the processing of threat-related stimuli [29,30], thus reflecting neural mechanisms of initial automatic (implicit) stimulus evaluation [31,32]. The fronto-parietal network, with the dorsolateral prefrontal cortex (DLPFC) and posterior parietal cortex (PPC, especially superior parietal cortex and inferior parietal lobes), plays a crucial role in cognitive control [33,34], suggesting that activation in DLPFC and PPC during IAT reflects cognitive control for overcoming implicit biases [25,35]. However, most research focusing on the neural basis of implicit associations used an indirect approach, applying regression analyses between IAT scores measured outside the scanner and neural activity from a separate task applied within the scanner [36].…”
Section: Introductionmentioning
confidence: 99%
“…Research further suggests that depressed individuals may exhibit heightened activity in MCS, and in emotion-related brain areas during self-referential processing in particular (Grimm et al, 2008; Lemogne et al, 2009; Renner et al, 2015). However, while some studies have found hyper activity in these areas in depressed patients (Lemogne, et al, 2009; Wagner, Schachtzabel, Peikert, & Bär, 2015), others have found hypo activity (Grimm, et al, 2008; Hooley et al, 2009; Johnson, Nolen-Hoeksema, Mitchell, & Levin, 2009; Renner, et al, 2015). Overall, reviews of the scientific literature suggest the possibility of hyperactive MCS during self-referential processing in depression (Nejad, et al, 2013), but mixed findings may be at least partly due to the limitations of some studies in which the valence of self-referential information was not accounted for in the research design.…”
Section: Relevance Of Self-face Processing For Understanding Suicide mentioning
confidence: 99%
“…Depressive episodes are characterized by preferential processing of negative information about a person's self (Bargh and Tota, 1988;Gotlib et al, 2004;Wagner et al, 2015). Thus, aging related microstructural abnormalities in the dACC and in the uncinate may disrupt functional connections within the NVS (Nejad et al, 2013;Steffens et al, 2011) and interfere with normalization of selfrepresentation, leading to residual negative self-referential thoughts (LeMoult et al, 2017;Renner et al, 2015;Schmaling et al, 2002).…”
Section: Discussionmentioning
confidence: 99%